(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2017)
With the message of Jesus Christ, ‘For I was hungry and you gave me to eat; I was thirsty and you gave me drink; I was a stranger and you took me, I was naked and you clothed Me; I was sick and I’ve researched; I was in prison and you came to Me. Then the righteous will answer him, saying, Lord, when did we see you hungry and we fed? Or thirsty and we gave you drink? Or when I saw you a stranger and took thee in, or naked and clothe You? Or when did we see you sick or in prison, and came unto thee? And the king answering, shall say unto them, Verily I say unto you, as you did it to one of these brothers of mine, too small, you have done it unto me (Mt 25: 35-40)’’, and founding the Church visibly at Pentecost, one of the constant work of the Christian Church was and is her revelation to the world of philanthropy and our neighbor. In the study below, we will try to explore some of the resorts main theoretical of his action Catholic social respectively to decipher what lately in the Western world, but also in the Oriental world comes together in a social doctrine of Ecclesia, starting from their own social thinking concepts. Our approach will be based - as we believe that it is natural – on the orthodox perspective of the dogmatic elements, especially anthropological, of Christian teaching, because when there is humanitarian in the world, the Church gives the measure a specific vision and echoes overriding attitude and action that ultimately come from God and are sanctioned as such by The Holy Scripture and Sacred Tradition.